105 EVALUATION OF A NEW PHYSIOTHERAPY-LED VESTIBULAR SERVICE EMBEDDED IN THE FALLS AND SYNCOPE UNIT. (25th October 2022) - Bademosi, O; Murphy, N; Byrne, L; Rice, C; Briggs, R; Lavan, A; O'Callaghan, S; Kenny, RA; Cunningham, C; Romero-Ortuno, R
Abstract: Background: Clinical presentations in the falls and syncope unit (FASU) are diverse and require a range of skillsets. Vestibular disorders amount to a significant proportion of presentations. In our FASU, we embedded a 0.5 FTE specialist physiotherapist with expertise in vestibular disorders to work alongside medical and nursing staff. We conducted a service evaluation of the activity of this new service. Methods: Retrospective Service Evaluation Approval was granted by our Research & Innovation Office. Pseudonymised data was collected corresponding to all new FASU physiotherapy service attendances between August 2021 and May 2022. Descriptive statistics were complemented by a binary logistic regression model to establish independent predictors of more than one physiotherapy session being required over the period. Results: There were 104 episodes recorded by the new service, corresponding to 101 unique patients. Mean age was 67.7 (SD 19.0, range 17-93), and 73.1% were women. 67% were treated and discharged in 1 session. On average, patients had had a mean of 2 falls prior to the consultation (range 0-25). 28.8% were using a walking aid, and 54.8% self-reported fear of falling. 25% of the referrals to the service were due to suspected vestibular disorders, 62% of which were directly treated by the physiotherapy service. The logistic regression model adjusting by age, sex, use of walking aid, number of falls, and fear of falling showed that only referral for vestibular disorder was an independent predictor of patients needing more than 1 physiotherapy treatment (OR 3.91, 95% CI 1.32-11.58, P=0.014). Conclusion: Vestibular disorders are common in FASU, and a majority can be treated by a specialist physiotherapy service. Repeated vestibular maneuvers are often needed in such patients. A responsive, embedded physiotherapy service in FASU can directly address this need and further evaluation will focus on the impact of this service on avoidance of ED attendances.